Variation of the BrO/SO2 molar ratio in the plume of Tungurahua volcano between 2007 and 2017 and its relationship to volcanic activity - Warnach, Simon; Bobrowski, Nicole; Hidalgo, Silvana; Arellano, Santiago; Sihler, Holger; Dinger, Florian; Lübcke, Peter; Battaglia, Jean; Steele, Alexander; Galle, Bo; Platt, Ulrich; Wagner, Thomas (Frontiers in Earth Science, 2019)
Recent long-term observations of the bromine monoxide (BrO) to sulphur dioxide (SO2) molar ratio in volcanic plumes have suggested a link between changes in the BrO/SO2 ratio and the volcanic activity. Nevertheless, understanding of the mechanisms determining this link is still limited due to the lack of studies on volcanic bromine release from the melt into the atmosphere. We present the results of 10 years (2007-2017) of observations of the BrO/SO2 molar ratio in the volcanic plume of Tungurahua volcano, Ecuador. Following the nearly continuous eruptive activity from 1999 to 2008, Tungurahua showed alternating phases of eruptive activity separated by periods of quiescence between late 2008 and March 2016, after which degassing intensity decreased below detection. By comparing the BrO/SO2 molar ratios collected from 13 eruptive phases to volcanic activity, this study aims to broaden the global observational database investigating their link. For this purpose, we combine three different methods to retrieve the BrO/SO2 molar ratio to analyse variations over different timescales. We identify a cyclic pattern in BrO/SO2 molar ratios for 11 of the 13 eruptive phases. The phases are initialised by low BrO/SO2 molar ratios between 2 and 6 x 10(-5) coinciding with vulcanian-type activity followed by a strong increase to ratios ranging between 4 and 17 x 10(-5) when eruptive dynamism shifts to strombolian. For five phases, we additionally observe a progressive decrease to the initial values of 2 to 5 x 10(-5) toward the end of the phase. This clear pattern indicates a connection between the BrO/SO2 molar ratio and eruptive dynamics. Based on our new data, we propose a conceptual model of the volcanic processes taking place at Tungurahua during the eruptive phases. Our data furthermore indicate that maximal BrO/SO2 molar ratios observed during each phase could be related to the input of volatile-rich magma into the active part of the volcanic system of Tungurahua. This study shows that long-term BrO/SO2 molar ratios can be used as a proxy for the volatile status as well as temporal evolution of the volcanic system.
Gesehen am 01.08.2019
Im Titel ist "2" tiefgestellt